Legal Regulation of Family Businesses between Local Legislative Disparity and Federal Integration (United Arab Emirates as a Model) - Al-Erian, Mohamed Ali Ahmed Mohamed (Journal of Legal and Political Studies, 2025)
The importance of family businesses in the UAE has led to the issuance of several local laws to regulate them, but it lacked some regulatory mechanisms, in addition to a set of other legal challenges Therefore, the Family Business Law of 2022 was issued, which aims to establish a comprehensive and easy legal framework to regulate the ownership and governance of family businesses in the country, and avoid the restrictions and many uncertainties in other existing In contrast, the study seeks to explore the position of legislators on the legal challenges facing the organization of family businesses in federal states - especially Kurdistan Region - Iraq. Keywords: Companies - Family ownership - Governance - Succession plan - Dispute resolution.
Keywords: Companies Family ownership Governance Succession plan Dispute resolution